Characterization of the aircraft bay/landing gear coupling noise at low subsonic speeds and its suppression using leading-edge chevron spoiler - Bennett, Gareth (Sage Publications, 2019)
When the aircraft opens the bay door to let the landing gear either drop or retract, the incoming flow will result in a significant amount of coupling noise from the bay and the landing gear. Here, an experimental study was reported to characterise the acoustic performance and flow field at low subsonic speeds. Also, we examined a passive control method leading-edge chevron spoiler to suppress the noise. The experiment was performed in a low-speed aeroacoustic wind, the bay was simplified as a rectangular cavity and the spoiler was mounted to the leading edge. Both acoustic and aerodynamic measurements were performed through two microphone arrays, pressure transducers and particle image velocimetry. It was found that installation of the landing gear model can attenuate cavity oscillation noise to some extent by disturbing the shear layer of the cavity leading edge. Moreover, acoustic measurement confirmed the noise control when the spoiler was used. In addition, a parametric study on the effects of chevron topology was performed, and an optimised value was found for each parameter. From the aerodynamic measurement, the noise reduction was explained from the perspective of fluid dynamics. It was observed that installation of the chevron can raise the leading-edge shear layer and break up the large-scale vortices, thereby controlling the Rossiter mode noise and the landing gear model noise at certain frequencies.
PUBLISHED
Keywords: Bay/landing gear; Coupling noise; Leading-edge chevron spoiler; Low subsonic speeds; Rossiter mode; Particle image velocimetry